(untitled) (Zoo Botanica, 2025)
Homeopathic medicines face criticism from the scientific community due to the lack of a clearly defined mechanism of action. The healing process, diagnosis of disorders, and selection of appropriate remedies are often not explained by practitioners. Furthermore, a significant objection to alternative medicines, particularly homeopathy, revolves around the extreme dilution of remedies in water or alcohol, resulting in the absence of detectable active molecules. In the present study the in vivo toxicological consequences of mother tincture and 30C and 200C potency of Chinchona (Chin.) and Arsenicum Album (ars.alb.) was evaluated, using Balb/c mice as an animal model. DNA damage in lymphocytes, bone marrow micronuclei formation, and sperm head anomalies were calculated to measure the potential drug-induced toxic effects of selected medicines. Data from the present study revealed a significant difference among the treatment groups. High damage was caused by positive control and 200C potency of both drugs showing 80.49±0.0 tail DNA % and high frequency of micronucleate bone marrow cells. Further study and research are needed to elucidate the mechanism of action of homeopathic medicines. The current data revealed that there is the least damage caused by negative control and mother tincture while notable damage is caused by positive control and 200C Potency which indicates that excess alcohol may act as a reason for damage.